2016
DOI: 10.1016/j.cois.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal migration during development and the amyloid precursor protein

Abstract: The Amyloid Precursor Protein (APP) is the source of amyloid peptides that accumulate in Alzheimer’s Disease. However, members of the APP family are strongly expressed in the developing nervous systems of invertebrates and vertebrates, where they regulate neuronal guidance, synaptic remodeling, and injury responses. In contrast to mammals, insects express only one APP ortholog (APPL), simplifying investigations into its normal functions. Recent studies have shown that APPL regulates neuronal migration in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Most importantly, however, the results on age-related changes in MG bouton densities reported by Peng and Yang 17 largely contrast with several earlier studies including serial EM analyses 10 , 11 , 13 showing that mature honeybee foragers have lower MB-calyx MG densities than younger bees (pruning effect). This discrepancy with earlier studies was also pointed out by Fahrbach and Van Nest 16 , but is largely ignored in the study by Peng and Yang 17 . In summary, we suggest that in the light of the serious methodological flaws outlined above the results by Peng and Yang on both maturation under normal conditions and after insecticide treatment should be viewed as preliminary and potentially flawed rather than conclusive.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Most importantly, however, the results on age-related changes in MG bouton densities reported by Peng and Yang 17 largely contrast with several earlier studies including serial EM analyses 10 , 11 , 13 showing that mature honeybee foragers have lower MB-calyx MG densities than younger bees (pruning effect). This discrepancy with earlier studies was also pointed out by Fahrbach and Van Nest 16 , but is largely ignored in the study by Peng and Yang 17 . In summary, we suggest that in the light of the serious methodological flaws outlined above the results by Peng and Yang on both maturation under normal conditions and after insecticide treatment should be viewed as preliminary and potentially flawed rather than conclusive.…”
Section: Resultsmentioning
confidence: 59%
“… 10 confirmed the size of projection neuron synaptic boutons in olfactory and visual subregions of the MB calyx of the honeybee using serial electron-microscopy based 3D reconstructions. However, fluorescent background staining and partly irregular shapes of olfactory and visual MG may further complicate quantitative confocal microscopy based measurements of synapsin-positive MG boutons 16 , 19 . Furthermore, as the laser energy at high confocal magnification is focused on a small volume, this may easily result in substantial bleaching of fluorophores within a small tissue block, especially when obtaining large 3D image stacks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic plasticity is considered to be a basis for learning and memory [ 5 – 7 ]. However, how synaptic structures relate to individual learning differences is not known [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of microglomeruli via immunolabelling has shown that age, age-dependent behavioural changes, temperature during pre-adult development, developmental changes and foraging activities of various social Hymenoptera lead to synaptic organizational and structural changes within the mushroom body calyces [ 8 , 21 24 ]. Recent work also showed that establishment of long-term memory is accompanied by changes in microglomerular density within the mushroom body of the insect brain, but this has only been examined for olfactory learning [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%